A review of phosphorus partition relations for use in basic oxygen steelmaking. (26th November 2017) - Drain, Phillip B.; Monaghan, Brian J.; Zhang, Guangqing; Longbottom, Raymond. J.; Chapman, Michael W.; Chew, Sheng J.
Abstract : Phosphorus removal in basic oxygen steelmaking is a significant problem for integrated steelmakers. Phosphorus removal is required due to its deleterious effect on the mechanical properties of steel. However, this is progressively becoming more difficult due to the increasing phosphorus content of many iron ores. Many studies have investigated dephosphorisation and published empirical phosphorus partition (LP ) equations for a range of conditions. The structure of these equations has been used to develop a new partition relation that allows the effect of minor slag constituents such as TiO2, Al2 O3 and V2 O5 on steel dephosphorisation to be tested. Al2 O3 was found to have a weak negative effect on the measured LP, except at the lower oxygen potential range tested, where a positive correlation was observed. Increasing TiO2 and V2 O5 contents were found to decrease the measured LP ; however, these correlations became less prevalent at the higher oxygen potential ranges tested.